Effect of gasoline additive on combustion and emission characteristics of an n-butanol Partially Premixed Compression Ignition engine under different parameters - An Lu (Nature Portfolio, 2021)
Abstract The experiments were conducted on a modified two-cylinder diesel engine to investigate the effects of excess-air coefficient (λ) and intake temperature (T in ) of different blending ratios (volume ratio of gasoline in the blends) on the combustion and emission characteristics of a Partially Premixed Compression Ignition (PPCI) engine. The results show that with the increase of gasoline blending ratio, the peak in-cylinder pressure (P max ), the peak in-cylinder temperature (T max ) and the peak heat release rate (HRR max ) of four test fuels all increase first and then decrease. When gasoline volume fraction is 10%, HC and CO emissions are the lowest. In addition, intake temperature (T in ) has a significant effect on the n-butanol/gasoline PPCI engine. With the increase of T in , the in-cylinder P max and HRR max of four test fuels gradually increase, the combustion phase advances and HC and CO emissions decrease, while NOx emissions increase slightly. Furthermore, as λ increases, the P max , T max and HRR max of the four test fuels show monotonously reducing trend. At the same time, mixture concentration has basically no effect on start of combustion (CA10), the combustion duration (CD) gradually extends, and HC and CO emissions increase.